THE IMPLEMENTATION OF PARENT’S RESPONSIBILITIES (HOMELESS) TOWARDS CHILDREN WELFARE ACCORDING TO REGULATION’S NO. 4 OF 1979 ON CHILDREN WELFARE IN BENGKULU CITY - Ardani Mahendra; Joko Susetyanto; Nur Sulistyo Budi Ambarini (Universitas Bengkulu, 2020)
The aims of the study entitled “Parents’ Responsibilities toward Children Welfare According to Regulations No. 4 of 1979 on Children Welfare (A Case Study on the Homeless in Bengkulu City) Analyzed by Using Theory of Role” were to analyze the implementation of parents’ responsibilities (homeless) toward children welfare in Bengkulu City, and to analyze the factors influenced the failure in performing parents’ responsibilities (homeless) in ensuring the welfare of children in Bengkulu City. The method used was empirical legal research with descriptive characteristic. The result of the study showed that: the implementation of parents’ responsibilities (homeless) in Bengkulu City toward the children welfare was below the acceptance standard level since a majority of parents (homeless) in Bengkulu City could not perform their responsibilities as parents, and the factors influenced the failure in performing parents’ responsibilities (homeless) in ensuring the children welfare in Bengkulu City were consisted of economic factor of the family, socio-economic role of the family, the family unity, attitudes and habits of parents, as well as communication between parents and children.